The efficacy of a computer assisted auditory training on the plasticity of the central auditory nervous system in hearing impaired children - Jalaei, Bahram (2016)
For improving auditory and speech skills, children with sensorineural hearing loss are required to use hearing amplifications devices and undergo a specific auditory rehabilitation program including auditory training. Computerized auditory training (CAT) has been shown to be effective in improving listening skills and enjoying for children. The Malay version of CAT, nevertheless, was not available for clinical applications. The main aim of the present study was to determine the effectiveness of a Newly-computerized Auditory Training (NAT) (when compared with regular auditory training, RAT) by recording speech-evoked auditory brainstem response (sABR) peaks in two groups of hearing impaired children before and after undergoing intervention. After completing the preliminary studies, the effectiveness of NAT in promoting neuroplasticity was tested. Eligible normal children (n=17, mean age = 5.6 ± 1.6 years), hearing impaired children who underwent NAT program (n=9, mean age = 7.00 ± 2.06 years) and hearing children who underwent regular auditory training (RAT) (n=11, mean age = 7.72 ± 1.48 years) were recruited. For pre-intervention session, parents of hearing impaired children (in both NAT and RAT groups) were instructed to fill in Meaningful Auditory Integration Scale (MAIS) questionnaire. All three groups of children then underwent sABR testing. Four months after the intervention, MAIS, myPRAT and sABR were recorded from the hearing impaired groups and the normal children were only required to undergo sABR testing. For the gender analyses, while significant differences in sABR results were found between men and women, no such effect was seen in children. In the main study, based on MAIS and myPRAT analyses, both NAT and RAT methods were found to be effective in improving auditory skills (p<0.05). However, the NAT method was found to be superior to RAT as indicated by stronger effect sizes. In sABR testing, the effect of hearing loss was clearly noted when the three groups were compared, particularly for peaks V and A (p<0.05). Based on the inter-group analysis, the mean latency of peak C improved after the intervention in the NAT group. For intra-group comparison of sABR, higher mean amplitude of peak V was observed in the NAT group after the intervention (as shown by the moderate effect sizes). No such pattern was seen in the RAT group. After the intervention, while significant differences in V/A slopes were found between normal and RAT groups, no notable differences were found between normal and NAT groups for all sABR composite onset measures. The possible reasons for these findings are discussed accordingly. The superiority of NAT method in promoting neuroplasticity is perhaps due to its materials and emphasis on the temporal aspect in the program. The present study offers several benefits to community, university and knowledge enhancement. The newly developed Malay version of NAT is now available to be used by clinicians as an alternative rehabilitative method for improving the listening skills of hearing impaired children.